The Implementation of Early Childhood Development Holistic Integrative in Optimizing Children's Essential Needs (Texas Journal of Multidisciplinary Studies, 2023)
This study entitled Implementation of Early Childhood Development Holistic Integrative in Optimizing Children's Essential Needs. This study used a qualitative type of research. This study aims to explain the implementation of Holistic Integrative activities since the role of Early Childhood Education is important in society in general and in families in particular, how to increase parents' knowledge in educating, caring for their children; besides, to find out the extent of the role of the POS PAUD education unit in implementing the Early Childhood Education program Holistic. The implementation of this Holistic Integrative Early Childhood development examines how planning is carried out by educational units. From the results of the data collection, five services/programs were implemented, namely education, care, nutrition, health and protection. Support families as the organizer of children's education at home and active participation in activities at school are supporting factors for the success of an integrative holistic approach on early childhood education